Senam Ibu Hamil dan Karakteristik Ibu Membantu Meningkatkan Persalinan - Justina Purwarini Acihayati (UIMA Press, 2020)
Introduction: One of the factors that can influence the delivery process is power, that can be trained by following the exercise pregnancy, because it has an impact on the mother during childbirth. Objective: The purpose of this research is to know the relationship between the characteristic and pregnant exercise with type of delivery. Method: This research is a descriptive correlative research with cross-sectional research and using no experimental quantitative design. Results: The result shows that there is a significant correlation between respondent characteristic (age, education, job, parity) and pregnancy exercise (p-value = 0,000) and type of delivery. Conclusion: Exercise pregnancy can help delivery so that mother can give birth without difficulty and keep mother and baby healthy after giving birth. Pregnancy exercise is needed by mothers especially in primigravida to prepare physically and mentally mother in facing childbirth